GEN-14 Dual regulation of histone methylation by mTOR complexes drives the progression of EGFR-mutant glioblastoma. (28th November 2020) - Masui, Kenta; Harachi, Mio; Muragaki, Yoshihiro; Mischel, Paul; Shibata, Noriyuki
Abstract: Trimethylation of histone H3 on lysine 27 (H3K27me3) is essential for ensuring proper gene expression and chromosomal function, and its aberration is associated with the pathogenesis of various brain tumors. However, it remains unclear how histone methylation is regulated in response to genetic mutation and intracellular metabolic status to facilitate the cancer cell survival in the most malignant IDH-wildtype glioblastoma (GBM). We herein report a novel mechanism of the specific regulation of H3K27me3 by cooperative action of two mechanistic target of rapamycin (mTOR) complexes in EGFR-mutant GBM. The level of H3K27me3 is significantly associated with the mutant EGFR signaling (EGFRvIII and EGFR amplification), and integrated analyses with histopathological, NGS and metabolome examinations revealed that both mTOR complexes (mTORC1 and mTORC2) upregulate H3K27me3 downstream of aberrant EGFR signaling. mTORC1 facilitates the protein translation of enhancer of zeste homolog 2 (EZH2), which is known as H3K27-specific methyltransferase. The other mTOR complex, mTORC2, remodels the metabolism of S-adenosylmethionine (SAM), an essential substrate for histone methylation. This synergistic mechanism causes H3K27 hypermethylation which subsequently promotes tumor cell survival both in vitro and in vivo mouse tumor model via regulation of the cell cycle-related tumor suppressor genes. The findings indicate that activated mTORC1 and mTORC2 complexes under aberrant EGFR signaling cooperatively contribute to the progression of IDH-wildtype GBM through specific epigenetic regulation, nominating them as an exploitable therapeutic target against cancer-specific epigenetics.